A Tumor Microenvironment Responsive Nanotheranostics Agent for Magnetic Resonance Imaging and Synergistic Photodynamic Therapy/Photothermal Therapy of Liver Cancer - Zhu, Yuwan; Deng, Mo; Xu, Nannan; Xie, Yingjun; Zhang, Xuewen (Frontiers in Chemistry, 2021)
Surgery is the main treatment for liver cancer in clinic owing to its low sensitivity to chemotherapy and radiotherapy, but this results in high mortality, recurrence, and metastasis rates. It is a feasible strategy to construct tumor microenvironments activated by nanotheranostics agents for the diagnosis and therapy of liver cancer. This study reports on a nanotheranostic agent (MONs@PDA-ICG) with manganese oxide nanoflowers (MONs) as core and polydopamine (PDA) as shell loading, with ICG as a photosensitizer and photothermal agent. MONs@PDA-ICG can not only produce ROS to kill cancer cells but also exhibit good photothermal performance for photothermal therapy (PTT). Importantly, O2 generated by MONs decomposition can relieve the tumor hypoxia and further enhance the treatment effects of photodynamic therapy (PDT). In addition, the released Mn2+ ions make MONs@PDA-ICG serve as tumor microenvironments responsive to MRI contrast for highly sensitive and specific liver cancer diagnosis.